2021
DOI: 10.20944/preprints202108.0423.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-Year Prospective Study of Occupational Health in the Intensivists of a COVID-19 Hub Hospital

Abstract: The COVID-19 pandemic has severely tested the physical and mental health of health care workers (HCWs). The various stages of the epidemic have posed different problems; consequently, only a prospective study can effectively describe the changes in the workers’ health. This repeated cross-sectional study is based on a one-year investigation (spring 2020 to spring 2021) of intensive care physicians in one of the two COVID-19 hub hospitals in Central Italy. Changes in their work activity due to the pan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Additionally, in our cohort, PTSD, insomnia, depression, and anxiety were not as severe as previous studies reported immediately after the outbreak of COVID-19 given their total scores on the subscales (Magnavita et al, 2020;Tan et al, 2020;Yin et al, 2020), while a series of studies conducted at different stages of COVID-19 in Central Italy showed that the psychological problems of health care workers were not significantly improved and that various problems and worries were perceived in their work and life (Magnavita et al, 2021a(Magnavita et al, , 2021b. Moreover, a recent review also reported that mental health issues, such as anxiety, depression, PTSD, and sleep disorders, had great impacts on health care workers, especially on their contacts with the public (Giorgi et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Additionally, in our cohort, PTSD, insomnia, depression, and anxiety were not as severe as previous studies reported immediately after the outbreak of COVID-19 given their total scores on the subscales (Magnavita et al, 2020;Tan et al, 2020;Yin et al, 2020), while a series of studies conducted at different stages of COVID-19 in Central Italy showed that the psychological problems of health care workers were not significantly improved and that various problems and worries were perceived in their work and life (Magnavita et al, 2021a(Magnavita et al, , 2021b. Moreover, a recent review also reported that mental health issues, such as anxiety, depression, PTSD, and sleep disorders, had great impacts on health care workers, especially on their contacts with the public (Giorgi et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…For nurses who remain in clinical practice, an obvious impact relates to psychosocial ramifications. As a repeated cross-sectional study on frontline workers in a COVID-19 hub-hospital reported, during the first wave, workload and compassion fatigue increased (Magnavita et al, 2020); with the development of the crisis, the heavy workload, isolation at work, uncertainty about safety procedures, and the abrupt decline in the time devoted to meditation and relaxation evolved to become prevalent causes of occupational stress (Magnavita et al, 2021a); one year after the baseline, an increased workload, isolation at work and in social life, lack of time for physical activity and meditation, and compassion fatigue are still reported in health workers and coexist with new worries for justice in safety procedures (Magnavita et al, 2021b). However, there is a significant variation in the extent to which nurses perceive risk in the clinical environment or events.…”
Section: The Risk Perceptions Of Nurse Clinicians For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation